GAF: From Design to Explanation of the Learning Process Using an Economics Gaming Intervention - Davis, Jason Stratton (Journal of Applied Business and Economics, 2018)
The Game Analysis Framework (GAF), which was created to provide a visual representation of ‘how’ and ‘why’ undergraduate students learn from the playing of educational economics games at tertiary level. GAF brings a unique perspective on the potential of games to provide a rich and complex learning environment because it focuses on the learning occurring within the game space. By introducing deliberative activity via an economics gaming intervention, the students become behaviourally, emotionally and cognitively engaged which enables them to move theory from being abstract to meaningful tools for deciphering economic reality.